Strengthening Students Character Through the Read-Aloud Technique Based on Islamic Stories - Sahriah Yunus (Journal of Education and Learning Sciences, 2026)
This study aims to analyze the development of students’ character through the “read aloud” technique based on Islamic stories in elementary madrasahs. The research focuses on the role of the teacher as a facilitator (scaffolding) in reading stories aloud and how this activity instills character values such as responsibility, patience, honesty, and independence in 27 students in grades 1–3. The method used was a qualitative approach with observation techniques during four read-aloud sessions using a series of Islamic character storybooks. The results of the study indicate that read-aloud activities can enhance students’ focus and engagement in learning. Students were observed listening attentively, actively responding through questions and answers, and demonstrating an understanding of the story’s content and moral values. The teacher’s use of intonation, expression, and emphasis was proven to help students grasp the story’s meaning. Additionally, asking inferential questions during and after the reading activity reinforced students’ understanding, as evidenced by their ability to answer 24 questions overall in the high-performance category. This activity also enriched students’ vocabulary through the introduction of new terms. The conclusion of this study indicates that the read-aloud technique based on Islamic stories is effective as a learning strategy for strengthening students’ character. Consistent implementation, supported by the teacher’s active role and a conducive learning environment, makes this method an innovative and practical alternative for shaping students’ character from an early age.